Desarrollo de una notación y herramienta de visualización de datos para mejorar la capacidad de análisis de procedimientos almacenados SQL - Carvajal-González, Erick (Instituto Tecnológico de Costa Rica, 2017)
The digital age in which we live is framed by a vertiginous development of both hardware and software, which means that in most of the companies the production processes are controlled by computer systems that every day support more operations and therefore become more complex, at the same time, advances in the storage capacity of computers allows companies to store more data, which are used for decision making. These data require technologies that allow efficient processing of information, which has made database technologies very important technologies for companies and also the SQL (Structured Query Language) language for query and data manipulation. Nowadays it is common to find much of the business logic of companies written in SQL language (e.g. stored procedures). The maintenance and evolution of the SQL code is a complex and expensive task for the companies because, among other factors, it takes time for a person to understand code already written and to be able to modify it without this having repercussions in other stored procedures. Therefore, the objective of this work has been to increase the ability to analyze SQL code and also reduce the time required to understand SQL statements taking advantage of the human brain's ability to interpret visual information in parallel, something that is not possible with the text which is processed sequentially. To achieve the above objective the present research focused on: a) creating a visual notation capable of graphically representing SQL code instructions, b) developing a tool that uses this notation to visualize SQL stored procedures, and c) validate that the use of visual notation saves time with regards to understanding code in text. Visual notation was designed considering principles that maximize cognitive effectiveness (i.e. speed, ease and precision with which information can be extracted), namely: semiotic clarity, perceptive discrimination, perceptual immediacy, visual expressiveness and graphic parsimony between others.
Proyecto de Graduación (Maestría en Computación) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Computación, 2017.
Keywords: Computación; Software; Almacén de datos; Procesamiento; Información; Research Subject Categories::TECHNOLOGY::Information technology::Computer engineering